PENERAPAN LITERASI DIGITAL MELALUI SUMBER ELEKTRONIK POTENSIAL GUNA MENINGKATKAN KEMAMPUAN MENULIS KARYA ILMIAH GURU DI SDN KOTA DEPOK - Fitri Senny Hapsari; Aliffia Teja Prasasty (IKIP SILIWANGI, 2020)
The purpose of this community service activity is to improve the teacher's ability to write scientific papers at State Elementary School of Ratu Jaya 4 Cipayung Depok. Increasing teacher professionalism through training in the application of digital literacy in utilizing potential electronic sources such as Google Scholar is indispensable in writing scientific papers. By doing this activity the teachers have more accurate references in collecting many materials that they can inspire in writing scientific papers, so that teachers have higher confidence to write scientific works with better quality and quantity. In addition to the team, this activity provided an opportunity to carry out one of the three dharma activities of the tertiary institution, which is to provide community service based on the problems faced by partners.